EFFECT OF AEROBIC EXERCISES AND RESISTANCE TRAINING ON GLUCOSE LEVELS IN TYPE 2 DIABETIC SUBJECTS. - Benkar, Aishwarya Pramod; Kanase, Smita Bhimrao (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Diabetes mellitus is a leading cause of death and disability in the world and its prevalence is predicted to rise to 10% by 2030. Hence, this study is conducted with objectives to find out the effect of aerobic exercises and resisted exercises on blood glucose levels in type 2 diabetes mellitus (T2DM) subjects and to compare the effect of both exercises on blood glucose level. Method: The comparative study was conducted at Krishna Institute of Medical Sciences Deemed University, Physiotherapy department, Karad. 30 participants with age group between 30 and 65 years were taken. Subjects were selected as per inclusion and exclusion criteria. Group A (15) participants were given aerobic exercise on static bicycle, and Group B (15) participants were given resistance training using dumbbells and weight cuffs for 5 days/week for 4 weeks. Diet recommendations were given to every participant. Results: Statistical analysis was performed using paired and unpaired t-test. Analysis showed statistically extremely significant difference in fasting blood glucose level and postprandial blood glucose level in both the groups (pâ‰¤0.0001). Conclusion: Thus, this study concludes that both aerobic exercises and resistance training prove to be beneficial in controlling blood glucose levels in T2DM subjects.